Solve the following equation with three variables:

3x + 2y - z = 1 ...(1)

x + 2y + z = 0 ...(2)

2x + y - 3z = - 1 ...(3)

### 1 Answer | Add Yours

The set of equations to be solved is:

3x + 2y - z = 1 ...(1)

x + 2y + z = 0 ...(2)

2x + y - 3z = - 1 ...(3)

(1) - (2)

=> 2x - 2z = 1 ...(4)

(2) - 2*(3)

=> -3x + 7z = 2 ...(5)

3*(4) + 2*(5)

-6z + 14z = 7

=> z = 7/8

x = 11/8

y = -9/8

**The solution of the set of equations is x = 11/8, y = -9/8 and z = 7/8**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes